(untitled) (Journal of Universal Science Research, 2026)
6-Aminopurine is an important heterocyclic compound exhibiting pronounced biological activity and serving as a precursor of plant growth regulators and coordination ligands. In this study, the benzylation reactions of 6-aminopurine were investigated under various reaction conditions in order to obtain selectively substituted derivatives. The influence of solvent polarity, base strength, temperature, and reagent ratio on the direction of N-alkylation was analyzed, with particular attention to substitution at the N7 and N9 positions of the purine ring. The synthesized benzylated products were isolated and structurally characterized using FT-IR, UV–Vis and NMR spectroscopy, confirming successful modification of the heterocyclic system.